Optimizing Learning with a Learning Management System for Mathematics Education Students at Universitas PGRI Silampari - Dodik Mulyono (Maslahah: Jurnal Pengabdian Masyarakat, 2026)
This community service aims to optimize the learning process for students of the Mathematics Education Program at Universitas PGRI Silampari through the implementation of a Learning Management System (LMS). In line with the rapid development of educational technology, LMS has become an effective solution to enhance the quality of learning that is more structured and interactive. In this activity, intensive training was conducted for both faculty members and students on the use of the LMS to access course materials, interact with instructors, and complete assignments online. The method used in this service is a participatory approach, involving faculty members and students directly in training and utilizing the LMS. The results of this service show that the use of LMS can improve the digital skills of both faculty and students and accelerate the learning process more flexibly and efficiently. Additionally, students can easily access course materials anytime and anywhere, while instructors can provide direct feedback and manage assignments more efficiently. The outcomes of this service are expected to make a positive contribution to improving the quality of education in the digital era and prepare students to face future educational challenges.